Ricoeur's hermeneutic phenomenology: an implication for nursing research - Charalambous, Andreas; Papadopoulos, Irena Rena; Beadsmoore, Alan (My University, 2008)
Researchers and educators are increasingly implementing qualitative research methods to investigate issues of concern and interest. Hermeneutics has risen as an option for the qualitative research paradigm particularly after the 1970s. The precedence of the sciences that have applied hermeneutics as their approach to investigation is provided with special reference to nursing. In the nursing science, hermeneutics have been used extensively as a qualitative research method to investigate a variety of issues, through the lived experiences of the participants. In this paper, we introduce important aspects of the philosophy of Paul Ricoeur and we discuss the reasons why we have applied this approach in our study titled 'Quality Nursing Care: perspectives of patients with cancer and the nursing response'. The arguments that are presented here can be generalised to fit other areas of Nursing Science. Through this paper our aim is not only to familiarise the reader with Ricoeur's work, but also to arrive at an appreciation of his philosophy as a methodological approach for future nursing research.
Keywords: Hermeneutic phenomenology; Paul Ricoeur; Narratives; Nursing research; Lived experiences; Ricoeur's interpretation theory